Political Dynamics and Islamic Leadership: KH Idham Chalid’s Influence during Indonesia’s New Order Era - Ohira, Norman; Putri, Luqyana Azmiya; Nurjaman, Andri; Witro, Doli; Alamin, Nurul; Alghani, Raid (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This article aims to highlight the role and struggles of KH Idham Chalid during the New Order era in Indonesia. This article employs a qualitative research method with a historical approach consisting of heuristics, criticism, interpretation, and historiography. Primary data sources were obtained from historical books, including Ahmad Barjie entitled “Dr. K.H. Idham Chalid Ulama Politisi Banjar di Kancah Nasional,” Arief Mudatsir Mandan with the title “Napak Tilas Pengabdian Idham Chalid: Tanggung Jawab Politik NU dalam Sejarah,” and Abdul Rahman Jaferi Rahmadi and Ahmad with the title “Elite Muslim Banjar di Tingkat Nasional.” Secondary data was obtained from scientific articles, books, and other relevant literature related to the research topic. The data analysis techniques used were data condensation, data presentation, and conclusion drawing. This study found that the role and struggle of KH Idham Chalid during the New Order era can be categorised into two categories. First, he fought within the New Order government. President Soeharto trusted KH Idham Chalid to hold strategic positions. One of them was to succeed the Family Planning (KB) programme. Second, he fought outside the New Order government through the education sector by establishing Darul Ma’arif in Cipete, South Jakarta, and Darul Qur’an in Cisarua, Bogor. KH Idham Chalid also frequently held religious study sessions that were widely attended by the public and played a role in the establishment of the Nahdlatul Ulama University (UNNU) in Bandung, which later evolved into the Nusantara Islamic University (UNINUS). Exploring the history of the educational institutions established by KH Idham Chalid could serve as a valuable subject for further research.